THE APPLICATION OF ASOCA ANALYSIS ON COMPETITIVENESS IMPROVEMENT STRATEGIES MUSLIM CLOTHING IN THE ASEAN REGION - Misrofingah; Sri Sugiarti (Kusuma Negara Business School, 2020)
Indonesia is a strategic country, including the fourth most populous country and the country with the most Muslim occupation. This makes Indonesia a target place for marketing products or being the most productive market share for Muslim clothing. Since globalization, trade has become free so that Muslim clothing business people face a lot of competition, namely domestic competition and foreign competition. To win the competition must have a specific strategy that is increasing the competitiveness of its products. The problem arises namely: how is the Islamic view of trade and how is the strategy to improve the competitiveness of Muslim clothing? The problem solving method is descriptive qualitative analysis which aims to provide a descriptive description of the subject based on data from the variables obtained by the group of subjects studied. Islam also knows free trade because the principle of trade in Islam is actually freedom. This means freedom in conducting transactions between buyers and sellers on the basis of pleasure (sincerity) and there is no coercion. Muslim clothing business players can compete with Muslim clothing products from other countries in ASEAN and outside ASEAN through the application of ASOCA analysis and need to also develop a good planning schedule in the short and long term.